A library-screening approach for developing a fluorescence sensing array for the detection of metal ions. Issue 15 (13th June 2016) - Smith, David G.; Sajid, Naveed; Rehn, Simone; Chandramohan, Ramya; Carney, Isaac J.; Khan, Misbahul A.; New, Elizabeth J.
Abstract : A four-membered array based on fluorescent thiophenes is capable of distinguishing transition metal ions. Abstract : Detection of individual metal ions is of importance across a range of fields of chemistry including environmental monitoring, and health and disease. Fluorescence is a highly sensitive technique and small fluorescent molecules are widely used for the detection and quantification of metal ions in various applications. Achieving specificity for a single metal from a single sensor is always a challenge. An alternative to selective sensing is the use of a number of non-specific sensors, in an array, which together respond in a unique pattern to each analyte. Here we show that screening a library of compounds can give a small sensor set that can be used to identify a range of metal ions following PCA and LDA. We explore a method for screening the initial compounds to identify the best performing sensors. We then present our method for reducing the size of the sensor array, resulting in a four-membered system, which is capable of identifying nine distinct metal ion species in lake water.